2022
DOI: 10.3389/fnut.2022.960239
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid increases lifespan and stress resistance via insulin/IGF-1 signaling pathway in Caenorhabditis elegans

Abstract: Numerous studies reported that betulinic acid (BA), a natural product extracted from birch bark, exhibited various beneficial effects in vitro. However, its pharmacological activities in aging are rarely understood. In this study, Caenorhabditis elegans was deployed as a whole animal model to investigate the impacts of BA on lifespan and stress resistance. Wild-type C. elegans were fed in the presence or absence of BA and tested for a series of phenotypes, including longevity, mobility, reproductive capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…In this study, the higher concentrations of astaxanthin were less effective for increasing the lifespan of C. elegans . Similar dose-response effects on lifespan were found for other bioactive compounds [ 61 , 62 ]. It is well established that both nutrients and beneficial/toxic chemicals may produce opposite consequences for an organism depending on the doses.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the higher concentrations of astaxanthin were less effective for increasing the lifespan of C. elegans . Similar dose-response effects on lifespan were found for other bioactive compounds [ 61 , 62 ]. It is well established that both nutrients and beneficial/toxic chemicals may produce opposite consequences for an organism depending on the doses.…”
Section: Discussionsupporting
confidence: 74%
“…Many pharmacological interventions used for their anti-aging effects increase the resistance to environmental stresses [17,18]. A recent study showed that supplementation with BetA increased the resistance to various environmental stresses in C. elegans [10]. To confirm that the beneficial effects of BetA against various stressors were conserved in the current organism model, the effects of BetA treatment on stresses, including heat shock, cold shock, oxidative stress, and starvation stress, were investigated (Figure 4).…”
Section: Treatment With Beta Did Not Change the Resistance To Thermal...mentioning
confidence: 99%
“…Extensive research in recent years has shown that it has antioxidant, anti-inflammatory, antiviral, and anticancer properties, making it an interesting subject for an investigation into its potential influence on lifespan [2,8,9]. Specifically, a recent study proved that BetA has an effect on longevity with an improvement in the healthspan due to its increased antioxidant activity and through its effects on the insulin/insulin-like growth factor-1 (IGF-1) signaling (IIS) pathway in Caenorhabditis elegans, a free-living nematode [10]. However, there is no evidence on whether BetA affects longevity in other organism models.…”
Section: Introductionmentioning
confidence: 99%
“…Pharyngeal pumping rates were measured based on previous studies. 23,24 Nematodes were placed on the surface of NGM plates with OP50, and the number of pharynx pumps was observed within 30 s, and counted on days 5, 10, and 15. Approximately 10 nematodes were randomly determined on each plate.…”
Section: Pharynx Pumping Abilitymentioning
confidence: 99%